mechanical systems design for a green tower - Masharqa, Shadi; Altalahma, Al-Mutaz; Sanad, Zaid (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2015)
The project is an environmental commercial tower includes many of the commercial, administrative and hotel activities in addition to the entertainment element. The tower consists of 19 floors with a total area of 2000 m2, and depends on its design and run on alternative and renwable energy to provide energy consumption. Includes work in the design of mechanical services of water and sewage networks and air conditioning system provider of energy and the project includes design of fire fighting system, and irrigation system by gray water after separated and processed. المشروع عبارة عن برج تجاري بيئي يتضمن العديد من الانشطة التجارية والادارية والفندقية بالاضافة لعنصر الترفيه حيث يتكون البرج من 19 طابق بمساحة اجمالية تبلغ 20000 م2 ويعتمد تصميمه وتشغيله على الطاقة البديلة والمتجددة لتوفير الطاقة. ويقوم المشروع على عمل الخدمات الميكانيكية وشبكات المياه والصرف الصحي ونظام تكييف الهواء ويشمل ايضا تصميم نظام اخماد الحريق والري بواسطة المياه الرمادية بعد فصلها ومعالجتها.
no of pages 124 , 29340, ميكانيك 4/2015 , in the store
Keywords: mechanical systems